A cell-based fluorescent assay for FAP inhibitor discovery. Issue 14 (15th July 2020) - Zhang, Bingye; Liu, Futao; Yang, Min-Fu; Xu, Jianfeng; Wang, Zheng; Zhang, Jianhua; Wang, Rongfu; Yang, Xing
Graphical abstract: Abstract: To facilitate the discovery of FAP inhibitors, a convenient cell-based fluorescent assay was developed by using a commonly available U87MG cell line and a FAP-specific substrate Suc-Gly-Pro-AMC. The assay enabled the fast determination of multiple IC50 s by simply incubating a solution of phosphate-buffered saline in a 96-well plate within 30 min. The substrate specificity, cross-reaction and other related conditions were systematically optimized. This method was successfully applied to determine the IC50 s of seven known inhibitors. The results are in consistence with the trend reported, which indicating that this practical assay is a valuable method to accelerate the discovery of FAP inhibitor.